Risk-Taking Behavior and Capital Adequacy in a Mixed Banking System: New Evidence from Malaysia Using Dynamic OLS and Two-Step Dynamic System GMM Estimators - Abdul Wahab H.; Saiti B.; Rosly S.A.; Masih A.M.M. (Routledge, 2024)
Indexed by WOS/SCOPUS/ERA